PENGEMBANGAN MODUL PERMAINAN TRADISIONAL UNTUK MENINGKATKAN KETERAMPILAN SOSIAL SISWA MTs DARUL HIKMAH PEKANBARU - Erin Astasia; Zulfan Saam; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This objective of this research to develop a traditional game module to improve social skills. The type of research used is Research and Development Research and Development (R&D) with six steps. To compile a perfect module, this study conducted validation tests on 2 fields of expertise, namely material validators, cultural & arts practitioners. The data collection technique in this study used a questionnaire technique in the form of a validation sheet. The data analysis technique used analysis qualitative and quantitative. The results of this study, have compiled a learning module with traditional game material which is divided into 5 materials. The overall result of the module feasibility test based on the material, culture & arts aspects shows that the assessment obtained an average value of 86.35%, which is stated to be very suitable for use as a service medium for the guidance and counseling study program.Key Words: Module Traditional Games, Social Skills